Ultra-broadband selective absorber for near-perfect harvesting of solar energy. (May 2021) - Liu, Haotuo; Xie, Ming; Ai, Qing; Yu, Zhihao
Highlights: Multi-layer Ni-Al2O3 solar absorber with metal-insulator-metal structure is presented. Absorbs solar energy from ultraviolet to near-infrared solar radiation band. Spectral absorption rate approximately 11% higher than traditional photonic crystal. Beneficial in areas such as solar thermal utilization and thermal photovoltaics. Abstract: Efficient absorption of solar spectral radiation is a key requirement in solar heat utilization. In an effort to achieve this goal, this study investigated slow light effect and magnetic polaritons, and analyzed other physical model coupling mechanisms in photonic crystals. To construct a class of two-dimensional layers of Ni-Al2 O3 as a pyramid array solar energy absorber, the high melting points of Ni and Al2 O3 were utilized to create an arrangement of absorbers with good thermal stability, low sensitivity to angle of incidence, and polarization independence. Based on AM1.5 solar spectral data, a simulation study of the photothermal absorption characteristics of this type of absorber in the 0.3–2.5 µm band was conducted. The results showed that the photothermal conversion efficiency is as high as 96.45%. Compared with the traditional single physical effect design, the conversion efficiency of this photonic crystal structure is increased by ~11%. Furthermore, increasing the concentration factor allows the absorber to maintain high efficiency even at high temperatures, which provides theoretical evidence for the efficient use of solar radiation. This work will be beneficial in several areas, including solar thermal utilization, thermal photovoltaics, absorber design, and radiator design in radiant refrigeration systems.